Middle-Range Theory of Occupational Stress in Health Professionals - Romanniny Hévillyn Silva Costa Almino RN, PhD; Ana Beatriz Pereira da Silva BSc; Anna Lívia de Medeiros Dantas RN, MSc; Harlon França de Menezes RN, PhD; Nanete Caroline da Costa Prado RN, MSc; Rebecca Stefany da Costa Santos RN, MSc; Roberta Keile Gomes de Sousa Manso RN, MSc; Thais Targino Ferreira BSc; Richardson Augusto Rosendo da Silva RN, PhD (SAGE Publishing, 2024)
Introduction Occupational stress affects health professionals; however, no literature was found on the middle-range theory for this outcome in health professionals. Methods Methodological study for the theoretical validation of a nursing diagnosis using the theoretical framework of Walker and Avant and the Betty Neuman systems models. The research was conducted in five stages: comprehension of the system model; selection and review of studies; development of the conceptual-theoretical-empirical structure; elaboration of a diagram and proposition of a nursing diagnosis; and evaluation of the empirical adequacy of the theory and validity of the system model. These steps were conducted using a scoping review and a sample of 138 articles selected in the Scopus, Web of Science, MEDLINE/PubMed, CINAHL, PsycINFO, LILACS, Science Direct, Cochrane Library, and Google Scholar databases. A data extraction instrument was developed, and study variables (attributes, antecedents, and clinical consequences) were analyzed using descriptive statistics (absolute and relative frequencies) and presented in tables. Results The middle-range theory comprised 16 concepts, 20 propositions, and one diagram. A total of 15 related factors, 29 defining characteristics, six at-risk populations, and one associated condition were indicated to propose the nursing diagnosis for occupational stress. Conclusion The middle-range theory supported elaborating elements to propose a nursing diagnosis for occupational stress.